Acute poisoning cases in emergency department of tertiary level hospital, Kathmandu - Baral, Dipti; Rajbhandari, S; Shrestha, A; Basyal, B; Prasad, PN (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: To determine the pattern of acute poisoning cases presenting to the Tribhuvan University Teaching Hospital (TUTH), Nepal.Method: A hospital based cross sectional study was carried out in the emergency department of TUTH analyzing the data of poisoning cases that attended emergency during one year period.Result: A total of 276 cases presented to the emergency during the period of one yearfrom February 9, 2010 to February 8, 2011. There were 111 males (40.2%) and 165 females (59.8%). Most of the patients (42%) were in age group of 20-30 years. 170 (61.6%) patients were married. Occupation wise, 31.5% of the cases were housewives, 30.1% were students and 14.5% were laborers. Most of the cases were suicidal (75.4%). Insecticide was the most common poison (40.2%) whereas in 46 patients the poisons could not be identified. Oral was the route of poisoning in almost all cases (99.6%). Most of the cases had presented within 12 hours of intake of poison. Previous psychiatric illness was present in 13 cases (4.7%). Only 12 cases (4.3%) were admitted.Conclusion: Females and young people are at greater risk of poisoning. The most common agent is insecticide and self-poisoning is the most common mode of poisoning.